Analysis of the spatio-temporal variability of spawning mackerel in the Northeast Atlantic - Gersom Costas (Frontiers in Marine Science)
The northeast Atlantic (NEA) mackerel (Scomber scombrus) is a commercially significant species, with expansive spawning migrations occurring along the continental shelf of northwestern Europe. To identify the main variables influencing the spatial distribution of mackerel eggs, this study analyzed data from egg surveys conducted by the Working Group on Mackerel and Horse Mackerel Egg Surveys (WGMEGS) of the International Council for the Exploration of the Sea (ICES). To achieve this objective, a Random Forest model was used to predict the presence of mackerel eggs based on temporal, geographical, and environmental variables. Applying the Random Forest model to the survey data revealed that the main variables affecting mackerel spawning were the bottom depth, latitude, temperature, and salinity. Subsequently, Quotient Analysis was used to determine the optimal ranges of the key variables identified as influencing mackerel spawning. The results demonstrated a clear preference for spawning at depths between 100 m and 200 m, as well as a consistent preference for the area between 43° and 44° North, corresponding to the Cantabrian Sea. Furthermore, the results indicated that mackerel exhibited a considerable range of temperature tolerance throughout the spawning process, with a preference for cooler waters in the Western area in recent years. Salinity seems to have an effect on spawning at salinities between 35.0 ppm to 35.5 ppm, but results were imprecise. These results contribute to our understanding of how environmental and geographical variables influence the spawning behavior of NEA mackerel.